Switching from intravenous to subcutaneous infliximab in patients with immune mediated diseases in clinical remission - Viazis, Nikos; Karamanakos, Anastasios; Mousourakis, Konstantinos; Christidou, Angeliki; Fousekis, Fotios; Mpakogiannis, Konstantinos; Koukoudis, Anastasios; Katsanos, Konstantinos; Christodoulou, Dimitrios; Cheila, Myrto; Tzouvala, Maria; Zacharopoulou, Eirini; et al. (Frontiers in Medicine, 2025)
AimTo report on the efficacy and safety of elective switching from intravenously (IV) to subcutaneously (SC) administered Infliximab (IFX) in patients with immune mediated diseases.MethodsRetrospective analysis of patients with Crohn’s disease (CD), Ulcerative Colitis (UC), Spondyloarthritis (SpA), Rheumatoid Arthritis (RA), Psoriatic Arthritis (PsA) and chronic plaque Psoriasis (PsO) who were receiving IFX-IV for maintenance of remission in tertiary referral centers and were switched to IFX-SC based on their physician’s choice. All patients with gastrointestinal and skin diseases were in clinical remission, while those with musculoskeletal disease had inactive disease or low disease activity. The primary endpoint was disease deterioration during a follow up period, of at least 6 months, according to disease specific composite measures.ResultsBetween April 2023 and April 2024, a total of 344 patients (CD = 136, UC = 62, SpA = 52, PsA = 38, RA = 7, PsO = 44, co-existence of more than one disease = 5) were switched from IFX-IV to IFX-SC. After a mean±SD follow up period of 8 ± 4 months, 12 patients (3.5%) discontinued treatment with IFX-SC. Five of them (1.5%) because of disease worsening and the remaining 7 (2.0%) because of the occurrence of side effects. All 332 other patients (96.5%) showed favorable response, none of them requested an unscheduled visit, or developed an adverse event (clinical or laboratory) or needed escalation of treatment.ConclusionElective switching from IFX-IV to IFX-SC seems to be an effective and safe approach in real-world every day clinical practice to maintain long-term clinical remission, inactive disease or low disease activity in patients with immune-mediated diseases.